RET rearrangement-positive pancreatic cancer has remarkable response to pralsetinib: a case report - Zhang, Tongyi; Wang, Hongwei; Cai, Zhiwei; Zhang, Siqi; Jiang, Chongyi (Frontiers in Oncology, 2023)
Because existing treatment options are ineffective, patients with metastatic pancreatic cancer often have a dismal prognosis. RET fusion occurred in just 0.6% of pancreatic cancer. The effectiveness of RET targeted treatment in the fusion of TRIM33-RET alone has not been reported in pancreatic cancer. Here we present a 68-year-old man with pancreatic cancer harboring TRIM33-RET fusion who responded remarkably to pralsetinib despite being intolerant to chemotherapy. To our knowledge, this is the first report on the clinical value of TRIM33-RET fusion in pancreatic cancer, which may benefit from the targeted therapy.